2007
DOI: 10.1515/bot.2007.047
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed invasions: conclusions and future directions

Abstract: In the introduction of this special issue of Botanica Marina, we established the scope of this topic around a series of questions, which also provided a framework for integrating the different contributions and a means of highlighting deficiencies in knowledge and understanding (Johnson and Chapman 2007). In defining challenges for the future and suggesting how those challenges might best be tackled to optimize returns on research investment, it is useful to revisit those questions under four main headings dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
1
4
0
5
Order By: Relevance
“…This is in accordance with other studies which have found that C. fragile can support many species of fauna (Schmidt & Scheibling, 2006;Drouin et al, 2011), and that introduced macroalgae in general do not have severe negative effects on diversity (e.g. Johnson, 2007;Thomsen et al, 2009;Engelen et al, 2013). Few taxa were completely absent from one of the host species, a pattern which has also been seen in other comparisons of non-native and native algae (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with other studies which have found that C. fragile can support many species of fauna (Schmidt & Scheibling, 2006;Drouin et al, 2011), and that introduced macroalgae in general do not have severe negative effects on diversity (e.g. Johnson, 2007;Thomsen et al, 2009;Engelen et al, 2013). Few taxa were completely absent from one of the host species, a pattern which has also been seen in other comparisons of non-native and native algae (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Introduced seaweeds can account for a significant proportion of the total aquatic flora (Johnson, 2007), and about 260 species have now been identified as alien to their native range (Hewitt et al, 2007). In some cases, these invaders, freed of the natural controls of their native range, can proliferate in new waterways, displace native species and significantly degrade ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive species in most cases dominate native algal communities, while eutrophication increases primary production, inducing blooms of opportunistic algae capable of rapidly exploiting the elevated amounts of nutrients (Duarte 1995;Johnson 2007;Johnson and Chapman 2007). These processes produce changes in the structure of algal communities, and consequently in the associated benthic fauna (Buschbaum et al 2006).…”
Section: Introductionmentioning
confidence: 99%